Genotype-phenotype correlations among BRCA1 4153delA and 5382insC mutation carriers from Latvia - Plakhins Grigorijs; Irmejs Arvids; Gardovskis Andris; Subatniece Signe; Rozite Santa; Bitina Marianna; Keire Guntars; Purkalne Gunta; Teibe Uldis; Trofimovics Genadijs; Miklasevics Edvins; Gardovskis Janis (BMC, 2011)
Abstract Background Mutations in the high penetrance breast and ovarian cancer susceptibility gene BRCA1 account for a significant percentage of hereditary breast and ovarian cancer cases. Genotype-phenotype correlations of BRCA1 mutations located in different parts of the BRCA1 gene have been described previously; however, phenotypic differences of specific BRCA1 mutations have not yet been fully investigated. In our study, based on the analysis of a population-based series of unselected breast and ovarian cancer cases in Latvia, we show some aspects of the genotype-phenotype correlation among the BRCA1 c.4034delA (4153delA) and c.5266dupC (5382insC) founder mutation carriers. Methods We investigated the prevalence of the BRCA1 founder mutations c.4034delA and c.5266dupC in a population-based series of unselected breast (n = 2546) and ovarian (n = 795) cancer cases. Among the BRCA1 mutation carriers identified in this analysis we compared the overall survival, age at diagnosis and family histories of breast and ovarian cancers. Results We have found that the prevalence of breast and ovarian cancer cases (breast: ovarian cancer ratio) differs significantly among the carriers of the c.5266dupC and c.4034delA founder mutations (OR = 2.98, 95%CI = 1.58 to 5.62, P < 0.001). We have also found a difference in the prevalence of breast and ovarian cancer cases among the 1st and 2nd degree relatives of the c.4034delA and c.5266dupC mutation carriers. In addition, among the breast cancer cases the c.4034delA mutation has been associated with a later age of onset and worse clinical outcomes in comparison with the c.5266dupC mutation. Conclusions Our data suggest that the carriers of the c.4034delA and c.5266dupC founder mutations have different risks of breast and ovarian cancer development, different age of onset and prognosis of breast cancer.